Factors Associated With Psychological Outcomes Among Vaccinated and Unvaccinated Health Care Workers Against COVID-19 Infection in Bangladesh - Alam, Md. Dhedharul; Paul, Sujan Kumer; Momi, Mahmuda; Ni, Li; Xu, Yi (Frontiers in Medicine, 2022)
Background: Vaccination of healthcare workers (HCWs) is recommended during the COVID-19 pandemic to reduce the risk of infection for themselves and their patients, as well as to encourage their patients to get immunized. We aimed to evaluate the psychological outcomes and associated factors among vaccinated and unvaccinated HCWs against COVID-19 infection in Bangladesh. Methods: From March to August 2021, an online nationwide survey was conducted with a total of 2038 Bangladeshi HCWs. Psychological outcomes were assessed via the GHQ-12, PHQ-2, GAD-2, PSS-4, PC-PTSD-5, ISI, and UCLA-LS. Results: Compared with unvaccinated HCWs (n=1058), vaccinated HCWs (n=980) had a statistically significant lower prevalence of general health problems (16.7% vs. 59.1%), depression (15.6% vs. 31.9%), post-traumatic stress disorder (22.3% vs. 30.8%), insomnia (23.8% vs. 64.9%), and loneliness symptoms (13.9% vs. 21.8%). Univariate analysis indicated that among vaccinated HCWs, residence in urban areas was an independent factor for all psychological outcomes except PTSD symptoms (P< 0.01 or 0.05), while working for less than 5 years was a risk factor for all psychological outcomes except stress symptoms (P<0.01 or 0.05). Among unvaccinated HCWs, being 18-29 years old and working for less than 5 years were common risk factors for all psychological outcomes except anxiety and insomnia symptoms (P≤0.01). Except for anxiety and stress symptoms, being frontline workers and providing direct service to infected patients were the most common risk factors for all psychological outcomes (P< 0.01 or 0.05). Multivariate analysis showed that among vaccinated HCWs, the female was a common risk factor for general health, anxiety, and loneliness symptoms (p<0.05). Except for anxiety and PTSD symptoms, living in urban areas was an independent risk factor for all psychological outcomes (p< 0.01). Being married was a significant risk factor for general health, depression, insomnia, and loneliness symptoms (p<0.01 or 0.05). Among unvaccinated HCWs, being a nurse was discovered to be a more common risk factor for symptoms of depression, anxiety, and stress (p<0.01 or 0.05). Conclusions: To control the infection and improve psychological outcomes, we recommend emphasizing the vaccinated to unvaccinated HCWs as soon as possible. They also required special attention, health-related education, and psychological support.